ENHANCING STUDENT COUNSELING THROUGH CO2C (COUNSELING TO CARE) DIGITAL INNOVATION - Rusmini; Sulikah; Yusria (Jurnal Isema : Islamic Educational Management, 2025)
Guidance and Counselling programs play a strategic role in supporting students' holistic development. This study aims to identify the implementation of the BK program at MAN 1 Kota Batam, its challenges, and its impact on student administration.  Using a qualitative descriptive approach, the research applied data collection methods through in-depth interviews, participatory observation, and documentation studies with the Team Guidance and Counselling of MAN 1 Kota Batam. The research findings reveal an innovative Guidance and Counselling program implementation, including student orientation services, individual and group counselling, and digital program development such as Co2C (Counselling to Care). Significant innovations include the use of leaf media for emotion management and barcode systems for online consultation. The program's impact encompasses increased mental health awareness, student administration responsiveness, and active student participation. The study concludes that MAN 1 Kota Batam has developed a comprehensive, systematic, and sustainable Guidance and Counselling program. This holistic approach goes beyond problem-solving, empowering student potential through technology integration, experimental methods, and multi-stakeholder collaboration.